Hyperbaric oxygen therapy for acute carbon monoxide poisoning patients with coma onset - Yangjuan Jia; Ning Han; Hui Guo; Hongling Li; Yunlei Du; Cancan Li; Jianguo Li (European Journal of Medical Research, 2025)
Abstract Objective This study aimed to evaluate the effects of coma on the prognosis and delayed encephalopathy in patients with acute carbon monoxide poisoning (DEACMP) and to analyze the predictive factors affecting the prognosis of these patients. Methods Patients with acute carbon monoxide poisoning were divided into comatose and non-comatose groups. The primary outcomes included clinical cure and the occurrence of DEACMP. Multivariate logistic regression analysis was performed to identify independent predictors of clinical outcome. Results Multivariate analysis indicated that coma (clinical cure: adjusted odds ratio [aOR] 0.24, 95% CI 0.12–0.47; DEACMP: aOR 42.5, 95% CI 7.99–789), longer the time from onset to the first HBOT (clinical cure: aOR 0.43, 95% CI 0.24–0.77; DEACMP: aOR 3.21, 95% CI 1.56–6.78) and abnormal chest CT findings (clinical cure: aOR 0.23, 95% CI 0.12–0.45; DEACMP: aOR 5.36, 95% CI 2.41–12.60) were associated with a lower rate of clinical cure and a higher proportion of DEACMP; and lower age was an independent predictor of clinical cure (aOR 0.96, 95% CI 0.94–0.98), but not of DEACMP (aOR 0.99, 95% CI 0.96–1.01). In comatose patients, both the duration of coma and abnormal chest CT findings were an independent factor for clinial cure (aOR 0.96, 95% CI 0.93–0.99; aOR 0.34, 95% CI 0.15–0.74) and DEACMP (aOR 1.09, 95% CI 1.06–1.14; aOR 4.93, 95% CI 1.67–16.30). Conclusion Coma and the duration of coma were significant predictors of clinical cure and DEACMP in patients; the older the patient, the longer the duration of coma, and the longer the time from onset to the first hyperbaric oxygen therapy (> 6 h), indicating that the patient’s prognosis is often worse; abnormal chest CT manifestations were also an independent risk factor for a poor patient’s prognosis.